Office Removal of a Subglottic Bread Clip - David E. Rosow; Si Chen (Case Reports in Otolaryngology)
Objective. The presence of an upper airway foreign body is an emergent, potentially life-threatening situation that requires careful but rapid evaluation and management. Organic or nonorganic material may typically be found in the pyriform sinuses or tongue base or may be aspirated directly into the tracheobronchial tree. We present here an unusual case report of a patient who accidentally ingested a plastic bread clip that was lodged in his subglottis for 15 months and report successful removal in the office under local anesthesia. Methods. Mucosal anesthesia was achieved with inhaled 4% lidocaine spray. Flexible laryngoscopic removal of the foreign body was then successfully accomplished. Results. The patient’s symptoms resolved completely following removal, with no sequelae. Conclusions. Office removal of airway foreign bodies is feasible and can be safely done with adequate topical anesthesia, but great caution and emergency planning must be exercised.